Synthesis of hexaphenylbenzene-based template assembled synthetic proteins - Madhu, Suresh; Madica, Krishnaprasad; Gonnade, Rajesh; Sanjayan, Gangadhar J (Tetrahedron Letters, 2019)
Template-assembled synthetic proteins (TASPs) synthesized from rigid templates have attracted attention due to their interesting structural architectures and potential biomedical applications. Herein, we report the design, synthesis and characterizations of TASPs based on hexaphenylbenzene template (HPB) having twelve peptide attachable axial-arms in its structure. The peptides were attached to all the axial-arms of the template in a single step using simple solution phase peptide coupling strategy. The reaction conditions were standardized systematically using simple amines from smaller size to larger ones. (C) 2019 Elsevier Ltd. All rights reserved.

Synthesis and biological activity of imidazole based 1,4-naphthoquinones - Choudhari, Dinkar; Salunke-Gawali, Sunita; Chakravarty, Debamitra; Shaikh, Samir R.; Lande, Dipali N.; Gejji, Shridhar P.; Rao, Pradeep Kumar; Satpute, Surekha; Puranik, Vedavati G.; Gonnade, Rajesh (New Journal of Chemistry, 2020)
Design and development of drugs in multi-drug resistant (MDR) infections have been of growing interest. We report the syntheses, and antibacterial and antifungal activities of imidazole-based 1,4-naphthoquinones (I-1 to I-4; 1-alkyl-2-methyl-1H-naphtho[2,3-d]imidazole-4,9-dione (alkyl = methyl to butyl)) and their precursors (B-3; N-(3-chloro-1,-dioxo-1,4-dihydronaphthalen-2-yl)acetamide) and A-1 to A-4; N-(3-(alkylamino)-1,4-dioxo-1,4-dihydronaphthalen-2-yl)acetamide (alkyl = methyl to butyl). Crystal structures of B-3, A-1 to A-3 and I-2 to I-4 were obtained through single crystal X-ray diffraction experiments. Electronic structure and charge distribution have further been characterized with the use of Density Functional Theory. Seven of these derivatives display a broad spectrum of antibacterial activity against few selected bacterial strains (Gram-positive and Gram-negative). As demonstrated MIC values with B-2 and B-3 against bacterial isolates were 8-64 mu g ml(-1) and those against pathogenic yeast, C. albicans, were observed in the range of 128-256 mu g ml(-1). MIC data of these derivatives suggest them to be promising against pathogens.

Solid-state NMR method for characterization of pharmaceutical eutectics - Hareendran, Chaithanya; Shaligram, Parth S.; Gonnade, Rajesh; Ajithkumar, T. G. (Physical Chemistry Chemical Physics, 2024)
Pharmaceutical eutectics are extremely useful for designing formulations, and currently, there are no techniques other than differential scanning calorimetry (DSC) that can confirm their formation. In this study, we demonstrate that 1H fast magic angle spinning (MAS) solid-state NMR (SSNMR) experiments can confirm the formation of eutectics by detecting their intermolecular hydrogen bonding interactions. 2D 1H-1H double quantum single quantum (DQSQ) correlation SSNMR experiment is demonstrated which can confirm the formation of pharmaceutical eutectics for which there are no techniques other than differential scanning calorimetry (DSC).

Structural characterisation, anticancer properties, and BSA binding of 2,6-dipyrazinylpyridines: Insights from experiment and theory - Enumula, Sreenivasulu; Shaikh, Javed; Shaikh, Amin; Sheikh, Kounsar N.; Tambe, Pranav; Lande, Dipali N.; Gejji, Shridhar P.; Shaligram, Parth; Gonnade, Rajesh; Bhadbhade, Mohan; Ahmed, Khursheed (Journal of Molecular Structure, 2026)
The phenyl-(2,6-di-2-pyrazinyl)pyridine derivatives (L1, L2) were synthesized using a one-pot Krohnke-type method, starting from 2-acetylpyrazine and substituted benzaldehydes. Their structures were characterized using a combination of spectroscopic (NMR, HRMS) and single-crystal X-ray diffraction techniques, complemented by density functional theory (DFT). Single-crystal X-ray diffraction reveals that L1 crystallizes in the C2/c space group (T = 296 K) with its supramolecular assembly being stabilized by C-H & ctdot;N and pi-pi stacking interactions, whereas L2 facilitates C-H & ctdot;N, N-H & ctdot;pi bifurcated, and pi-pi* interactions. The bio-interaction properties of L1 were studied using fluorescence spectroscopy with bovine serum albumin (BSA) as a model protein. Fluorescence studies demonstrated L1 induces static quenching of BSA, with a binding constant of 5.15 x 104 mol & sdot;dm-3. Synchronous and three-dimensional fluorescence spectra further demonstrated that L1 brings forth significant conformational changes in BSA. The compounds were evaluated for cytotoxicity against the HCT-116 human colorectal cancer cell line.
Keywords: 2; 6-dipyrazinylpyridines; Bovine serum albumin interaction; Cytotoxicity (HCT-116 cells); Density functional theory; Halogenated derivatives; Single-crystal X-ray diffraction